The Impact Analysis of Fire Disaster at Tamangapa, Makassar - Bilwalidayni Ikbal; Cahyono Kaelan; Armyn Nurdin (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This research is a type of qualitative research using a descriptive phenomenological approach. This research aims to determine the impact of the fire disaster of the Tamangapa garbage dumpsite, Makassar. The results of the analysis showed that the health impacts that people felt were coughing, shortness of breath, dizziness, headaches and sore eyes. The environmental impact felt by the community is the presence of smoke, smog and foul odors. The social impact felt by the community is reduced income and schools are closed. Fire disasters for landfills have resulted in environmental damage which also has an impact on health and social issues, especially for people who live ≤ 500 meters from the landfill, experiencing the heaviest impact